2014
DOI: 10.1016/j.jvs.2014.10.091
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Salivary Cotinine and Cardiovascular Biomarkers Among Nonsmokers and Current Smokers: Cross-sectional Study of 10,081 Participants

Abstract: 21.8 mm) than +FH with male relatives (19.9 mm, p = .007). Furthermore the prevalence of AAA was significantly higher among +FH (6.7%) compared with ÀFH (3.0%) with an odds ratio (OR) of 2.2 (95% CI: 1.6 to 3.2, p < .001) and +FH with female relatives with AAA had a more than two and a half times increased prevalence of AAA compared with +FH with male relatives with AAA with an OR of 2.65.Conclusions: First-degree male relatives of AAA patients have wider aortas and a twofold higher prevalence of AAA compared … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
6
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 0 publications
1
6
1
Order By: Relevance
“…25 For IL-6, our findings are consistent with other studies also reporting generally null associations. 26,27,30 Our findings for fibrinogen are mostly inconsistent with other studies, as American, 30,33 Scottish, 31 Greek, 32 and Japanese 35 cohort studies have shown significant positive associations between SHS exposure and fibrinogen. Our study, however, is consistent with another study that found no association between SHS exposure (evaluated by serum cotinine) with fibrinogen among 3221 NHANES (1999)(2000)(2001)(2002) participants aged 20 years and older.…”
Section: Discussioncontrasting
confidence: 96%
See 3 more Smart Citations
“…25 For IL-6, our findings are consistent with other studies also reporting generally null associations. 26,27,30 Our findings for fibrinogen are mostly inconsistent with other studies, as American, 30,33 Scottish, 31 Greek, 32 and Japanese 35 cohort studies have shown significant positive associations between SHS exposure and fibrinogen. Our study, however, is consistent with another study that found no association between SHS exposure (evaluated by serum cotinine) with fibrinogen among 3221 NHANES (1999)(2000)(2001)(2002) participants aged 20 years and older.…”
Section: Discussioncontrasting
confidence: 96%
“…51 Several studies have assessed the relationship between SHS and hsCRP. Among adults, SHS exposure was associated with hsCRP levels in most studies, 27,[29][30][31][32] although a few studies found no association. 26,28,33 Among children and adolescents, SHS was positively associated with hsCRP in National Health and Nutrition Examination Survey (NHANES), 24 but not in other smaller studies.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Household response rates were 81% in 1995, 76% in 1998, 68% in 2003, and 61%–64% between 2008 and 2010 [ 20 ]. The methodology has been described in detail previously [ 16 , 21 ]. Briefly, a two-stage process was used: a face-to-face interview was conducted by trained staff during which they collected information on demographics (including age, sex, postcode of residence, education, employment and income) and lifestyle (including alcohol intake, physical activity and smoking status) via computer assisted personal interviewing (CAPI), followed by a visit by a nurse who collected measurements (including height, weight and blood pressure) using standard operating procedures.…”
Section: Methodsmentioning
confidence: 99%